2023
DOI: 10.1111/ppl.13878
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the environmental factors shaping lateral root development

Abstract: Roots are important organs of plants. Plants rely on roots for water, nutrients, and organic salts. In the whole root system, lateral roots (LRs) account for a large proportion and are critical to the development of the plant. Many environmental factors affect LR development. Therefore, a systematic understanding of these factors can provide a theoretical basis for creating optimal growth conditions for plants. In this paper, the factors affecting LR development are systematically and comprehensively summarize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Soil-borne Trichoderma spp. are ubiquitous in soil worldwide, and have been used as biocontrol agents against pathogens for decades [23,31,[37][38][39]. However, the potential utility of Trichoderma spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Soil-borne Trichoderma spp. are ubiquitous in soil worldwide, and have been used as biocontrol agents against pathogens for decades [23,31,[37][38][39]. However, the potential utility of Trichoderma spp.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that beneficial Trichoderma spp. induce resistance against pathogens [31][32][33]. However, their effect on inducing insect resistance remains largely unexplored.…”
Section: T Virens Colonization Suppressed Insect Defensementioning
confidence: 99%
“…The growth promotion activities of encapsulated doses (125, 375, and 500 µL L −1 ) of 2-nonanone and 2-tridecanone were tested in seedlings of L. sativa for 14 days. The life and adaptation of plants strongly depend on the strength of their root system [34,35]. The root system has an essential role in acquiring nutrients, water, and organic salt [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…The life and adaptation of plants strongly depend on the strength of their root system [34,35]. The root system has an essential role in acquiring nutrients, water, and organic salt [34,35]. Therefore, a radical system is pivotal to plant soil exploration under climate change conditions [34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation